1998
DOI: 10.1016/s0375-9601(98)00577-5
|View full text |Cite
|
Sign up to set email alerts
|

Localized moving breathers in a 2D hexagonal lattice

Abstract: We show for the first time that highly localized in-plane breathers can propagate in specific directions with minimal lateral spreading in a model 2-D hexagonal non-linear lattice. The lattice is subject to an on-site potential in addition to longitudinal nonlinear inter-particle interactions. This study investigates the prediction that stable breather-like solitons could be formed as a result of energetic scattering events in a given layered crystal and would propagate in atomic-chain directions in certain at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
94
2
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 7 publications
7
94
2
1
Order By: Relevance
“…This was motivated by a previous study [17], where the superconducting properties of cuprates were correlated to the existence of linear chains of atoms, which were conjectured to transport one-dimensional nonlinear waves. Our results provide a realization of these waves in the form of mobile discrete breathers, which we have already established in the hexagonal lattice case [13].…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…This was motivated by a previous study [17], where the superconducting properties of cuprates were correlated to the existence of linear chains of atoms, which were conjectured to transport one-dimensional nonlinear waves. Our results provide a realization of these waves in the form of mobile discrete breathers, which we have already established in the hexagonal lattice case [13].…”
Section: Introductionsupporting
confidence: 74%
“…Radiation to the adjacent chains of atoms is, in principle, to be expected. Nevertheless, we recently found that moving breathers can exist in hexagonal 2D lattices, and showed that they show a remarkable transverse focusing effect [13].…”
Section: Moving Breathersmentioning
confidence: 99%
“…Note that these fixed oxygens are really off the plane, so that the distances to the K atoms are computed in full 3D Euclidean space (the z-coordinate being constant). This is in contrast with our initial model in [14], where we placed 6 fixed atoms in the plane, interacting through a Morse potential. Using the intuition gained about discrete breathers in 1D models, it was judged that it was not the particular shape of the nonlinear potentials used which was of main importance.…”
Section: Longitudinal Moving Breathers In 2d Latticesmentioning
confidence: 84%
“…In [14] we showed for the first time how localized excitations of longitudinal type can move in a 2-D lattice. These lattice modes appear to be the mobile version of intrinsic localized modes [24], more commonly known as discrete breathers.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation